2019
DOI: 10.1186/s12882-019-1445-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microparticle profiles by vitamin D receptor activation in chronic kidney disease – a randomized trial

Abstract: Background Microparticles (MPs) are biomarkers and mediators of disease through their expression of surface receptors, reflecting activation or stress in their parent cells. Endothelial markers, ICAM-1 and VCAM-1, are implicated in atherosclerosis and associated with cardiovascular risk. Chronic kidney disease (CKD) patients have endothelial dysfunction and high levels of endothelial derived MPs. Vitamin D treatment has been reported to ameliorate endothelial function in CKD patients. We aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Mörtberg and colleagues have recently shown that circulating concentrations of PMPs expressing CD40 ligand were positively associated with the severity of chronic kidney disease, and the concentration of CD40 ligand + PMPs is inversely correlated with estimated glomerular filtration rate (eGFR) [35]. In other studies, CD40 ligand + PMPs of CKD patients can be reduced by the vitamin D2 derivative, paricalcitol [36], or lipid-lowering treatment (LLT) with simvastatin in the settings of diabetes mellitus (DM)-CKD [34].…”
Section: Cd40 and Cd40l As Markers Of Renal Function In Kidney Diseasementioning
confidence: 99%
“…Mörtberg and colleagues have recently shown that circulating concentrations of PMPs expressing CD40 ligand were positively associated with the severity of chronic kidney disease, and the concentration of CD40 ligand + PMPs is inversely correlated with estimated glomerular filtration rate (eGFR) [35]. In other studies, CD40 ligand + PMPs of CKD patients can be reduced by the vitamin D2 derivative, paricalcitol [36], or lipid-lowering treatment (LLT) with simvastatin in the settings of diabetes mellitus (DM)-CKD [34].…”
Section: Cd40 and Cd40l As Markers Of Renal Function In Kidney Diseasementioning
confidence: 99%
“…Researchers studying the transport mechanisms used by myokines to reach the bloodstream have suggested that they are transported by EVs [ 88 ]. This makes sense, as it is known that the muscle, like any other tissue in the body, releases EVs in the course of pathological conditions such as cancer [ 89 ], HIV [ 90 ], heart attacks [ 91 ], and kidney disease [ 92 ], or due to specific stimulus such as exercise [ 93 ]. Some authors have even suggested that the beneficial health effects that occur as a result of exercising are due to the content of myokines and miRNAs, among others, which are produced by muscle cells and transported via EVs [ 94 , 95 ].…”
Section: Extracellular Vesicles In Undernutritionmentioning
confidence: 99%
“…Treatment of an activated (inflamed) endothelial cell line with VD suppresses gene expression for tissue factors and adhesion molecules. 122 Furthermore, treatment with VD in patients with chronic kidney disease who have endothelial dysfunction with high serum levels of circulating microparticles leads to a significant reduction in the level of microparticles; 123 it has also been found to inhibit microparticle release from a human endothelial cell line after their exposure to oxidative stress. 124 Moreover, supplementing high doses of VD decreases thrombin production in severely VD deficient patients.…”
Section: Dovepressmentioning
confidence: 99%